PENGARUH KOMPETENSI KEPRIBADIAN GURU PPKn TERHADAP PERILAKU SISWA SMA NEGERI DI KOTA PEKANBARU - Oktavani, Gita Dwi; Erlinda, Sri; ', Gimin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack : This research is motivated by problems that arise from interviews conducted by researchers that the violations are often done by students is like late, unplug in certain lessons, attribute offense, talking with friends, not making tasks, cheating, trespassing and eating at canteen during school hours , some even caught smoking in the school environment. This study aims to determine the influence of personality competence of civic education teachers on the behavior of high school students in Pekanbaru City. This research method is descriptive quantitative. The instrument used is a questionnaire consisting of 29 statements about teacher personality competence and 20 statements about student behavior. Data were analyzed by using simple linear regression. Thus the hypothesis which states